Mathematics Anxiety Factors and Their Influence on Performance in Mathematics in Selected International Schools in Bangkok - Shaikh, Shamim Nisar (Journal of Education and Vocational Research, 2013)
The objectives of this study were: 1) To determine the level of Performance in Mathematics of Grade 4 students in selected international schools in Bangkok in terms of Knowledge skills, Comprehension skills, Application skills, Analysis skills, Synthesis Skills, and Evaluation skills; 2) To determine the level of Mathematics Anxiety of Grade 4 students in terms of Cognitive factors, Psychological factors, Physical factors, and Environmental factors; 3) To investigate the influence of Math Anxiety factors on Performance in Mathematics. The study utilized the descriptive method. The instrument employed for collecting the data was a Math Anxiety Opinionnaire (MARS) developed by Richardson and Suinn (1972), and its many shorter derivations (Alexander & Martray, 1989; Plake & Parker, 1982; Rounds &Hendel, 1980; Suinn & Winston, 2003). The Math Test was based on the curriculum of Grade 4. The statistics used for the treatment of the data were mean, standard deviation(s.d.), standard error mean (s.e.mean), coefficient of variation(C.V.),rank and ANOVA. The results showed that the highest level of Performance in Mathematics is in the Comprehension skills and the lowest is Knowledge skills. Environmental factors produce the highest level of anxiety among the students. Physical factors had the highest influence on Performance in Mathematics.